Validation of the Musculoskeletal Health Questionnaire in inflammatory arthritis: a psychometric evaluation. (10th August 2018) - Norton, Sam; Ellis, Benjamin; Santana Suárez, Beatriz; Schwank, Samana; Fitzpatrick, Ray; Price, Andrew; Galloway, James
Abstract: Objectives: The Musculoskeletal Health Questionnaire (MSK-HQ) is a recently developed Patient Reported Outcome Measure for use across patients with musculoskeletal conditions. This study provides a validation of the MSK-HQ examining construct validity and reliability in inflammatory arthritis. Methods: 287 adults with inflammatory arthritis completed the MSK-HQ and other Patient Reported Outcome Measures at baseline and after 3 months. Construct validity was assessed using item response theory methods. Concurrent validity was considered in relation to the HAQ and EuroQol-5D in all patients, as well as the RA Impact of Disease (RAID), PsA Impact of Disease scales, and AS Quality of Life Questionnaire (ASQoL) in disease subtypes. Results: The MSK-HQ was approximately normally distributed with no evidence of floor or ceiling effects. A unidimensional structure was confirmed. Two items were less weakly related to the latent musculoskeletal health variable, providing some evidence of multidimensionality. Reliability was high (α = 0.93). The total score correlated highly with the HAQ ( r = −0.81) and EuroQol-5D index ( r = 0.80) in all patients, RAID in RA patients ( r = −0.88), PsA Impact of Disease in PsA patients ( r = −0.88), and ASQoL in AS patients ( r = −0.86). Test-retest reliability was high ( r ICC = 0.73). Conclusion: This study provides evidence for the validity and reliability of the MSK-HQ in people with inflammatory arthritis. The major advantage of the MSK-HQ is that it is not disease specific and has high content validity in rheumatological conditions. The MSK-HQ score will be of value in clinical rheumatology practice, providing a measure that can be used across disease areas.